Lekarz Hermiasz z Kos w świetle źródeł epigraficznych - Kaczyńska, Elwira (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The aim of my article is to discuss six Hellenistic inscriptions which mention Hermias, son of Emmenidas, a distinguished physician from Kos. Two longer honorary inscriptions are connected with Hermias’ five-year stay on the island of Crete as a public doctor. The epigraphic sources in question will be carefully reviewed, translated into Polish and commented on the article.